Disney's A Christmas carol [videorecording (DVD)] - Zemeckis, Robert, 1952-; Zemeckis, Robert, 1952-; Zemeckis, Robert, 1952-; Dickens, Charles, 1812-1870 (Walt Disney Studios Home Entertainment, 2010)
A 3D computer animated motion-capture version of the classic Christmas story. Ebenezer Scrooge begins the Christmas holiday with his usual miserly contempt, barking at his faithful clerk and his cheery nephew. But when the ghosts of Christmas Past, Present, and Yet to Come take him on an eye-opening journey revealing truths Old Scrooge is reluctant to face, he must open his heart to undo years of ill will before it's too late.